"Passwords protect my stuff"—a study of children's password practices. Issue 1 (13th December 2019) - Choong, Yee-Yin; Theofanos, Mary F; Renaud, Karen; Prior, Suzanne
Abstract: Children use technology from a very young age and often have to authenticate. The goal of this study is to explore children's practices, perceptions, and knowledge regarding passwords. Given the limited work to date and that the world's cyber posture and culture will be dependent on today's youth, it is imperative to conduct cyber-security research with children. We conducted surveys of 189 3rd to 8th graders from two Midwest schools in the USA. We found that children have on average two passwords for school and three to four passwords for home. They kept their passwords private and did not share with others. They created passwords with an average length of 7 (3rd to 5th graders) and 10 (6–8th graders). But, only about 13% of the children created very strong passwords. Generating strong passwords requires mature cognitive and linguistic capabilities which children at this developmental stage have not yet mastered. They believed that passwords provide access control, protect their privacy and keep their "stuff" safe. Overall, children had appropriate mental models of passwords and demonstrated good password practices. Cyber-security education should strive to reinforce these positive practices while continuing to provide and promote age-appropriate developmental security skills. Given the study's sample size and limited generalizability, we are expanding our research to include children from 3rd to 12th graders across multiple US school districts.